Practise of AITAB in Vehicle Purchasing at Bank Rakyat / Nur Izzati Hafizah Mat Tohid - Mat Tohid, Nur Izzati Hafizah (Academy of Contemporary Islamic Studies (ACIS), 2018)
The understanding from both parties is important in contract, if one of them give a wrong information, it will be misunderstanding among them. Beside both parties need to know the responsibility. The responsibility towards ijarah asset is determined by referring to the status of ownership held by parties to the contract. Such responsibility covers the aspect of maintenance and protection towards the underlying assets throughout the terms of ijarah. The asset meant here is the vehicle that corresponds with the studied product which is al-Ijarah Thumma al-Bay (AITAB). Such product is based on ijarah contract; thus, it must fulfill the crucial elements in ijarah and bay contract, its conditions, and must as well avoid any shariah prohibitions. As the Islamic Hire Purchase Act is absent, hence Conventional Hire Purchase Act 1967 must be followed in order to avoid any breach of contract. The impact of it is that there is a contradiction between the shariah and law enforcement regarding the risks of the responsibilities of contracting parties towards the asset where such risks are now under the responsibility of consumers whereby supposedly according to original theory of ijarah, such risks shall be assumed by the owner. Hence, the main objective of this study is to identify the position of leased asset and responsibility in ijarah according to shariah and law, as well as to evaluate the compliance of the practice of AITAB in terms of assets, responsibilities at Bank Rakyat as well as to analyze the method applied by the bank in determining the ownership of AITAB asset. The design of the study is qualitative by applying the approach of content analysis and case study. AITAB product in Bank Rakyat was chosen in this study. Data are collected through document analysis of Islamic jurisprudence books, journals and semi-structural interviews. The findings of this study are that the practice of assuming the responsibilities among contracting parties to the contract in Bank Rakyat have yet to fulfill the responsibility guidelines as desired in the contract of ijarah. The implication of this study illustrates the need of specific provision for AITAB products in handling such issues.